2022
DOI: 10.30737/ekonika.v7i2.2979
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Iklan Media Elektronik, Brand Ambassador dan, Brand Image Terhadap Minat Beli (Studi Kasus Konsumen Mie Lemonilo di Kota Surakarta)

Abstract: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh iklan media elektronik, brand ambassador dan, brand image terhadap minat beli pelanggan. Dengan maraknya persaingan sengit dalam penjualan mi instan, para pelaku bisnis harus memperkuat metode pemasarannya. Teknik pemasaran yang digunakan dalam penelitian ini adalah dengan menggunakan iklan media elektronik yang dibantu oleh brand ambassador untuk menyebarkan informasi tentang barang. Responden survei ini adalah pelanggan Mie Lemonillo di kota Surakar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Proximity to consumers makes Mie Sedaap market power during intense competition. This is relevant to the results of previous researchers Gunawati (2022) and Arifin & Setyaningrum (2022) which state that the brand image variable partially has a positive and significant influence on purchasing decisions. And Anggraeni & Sabrina (2021) state that brand image has no positive and insignificant effect on purchasing decisions.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…Proximity to consumers makes Mie Sedaap market power during intense competition. This is relevant to the results of previous researchers Gunawati (2022) and Arifin & Setyaningrum (2022) which state that the brand image variable partially has a positive and significant influence on purchasing decisions. And Anggraeni & Sabrina (2021) state that brand image has no positive and insignificant effect on purchasing decisions.…”
Section: Introductionmentioning
confidence: 56%
“…This result is also supported by the results of the analysis of respondents' answers, especially on the reputation indicator with the statement "Mie Sedaap always releases new products and innovations so I want to always try them". It is the same with research (Arifin & Setyaningrum, 2022) entitled "Analysis of the Influence of Halal Labeling, Price, Promotion, Taste, and Brand Image on the Purchase Decision of Kanzler Sausages by Millennials (Studies on Indomaret Sragen Supermarket Consumers)", furthermore "The Influence of Advertising Electronic Media, Brand Ambassador, and Brand Image on Purchase Intention (Case Study of Lemonilo Noodle Consumers in Surakarta City)" (Gunawati, 2022), on the results (Waluyo et al, 2023) entitled "The Effect of Product Variants and Brand Image on Decisions Purchasing Pucuk Harum Tea in Langsa City" and the last one entitled "The Effect of Brand Image and Product Quality on Purchase Decisions for TVS Motorcycles" (Pasaribu, 2022) researchers found that brand image variables had a positive and significant effect in this study. Shared or partial brand image has a significant and positive influence on consumer choice.…”
Section: The Effect Of Brand Image On Purchasing Decisionsmentioning
confidence: 74%
See 2 more Smart Citations
“…(Adiyani et al, 2021). As can be seen today, many business actors are now taking advantage of technological sophistication in order to be able to compete with other business actors, one of which is in terms of marketing (Gunawati et al, 2022).One form of marketing that uses digital technology is digital marketing. Digital marketing is a marketing strategy that uses digital media to promote products or services online to potential consumers (Susanti et al, 2023).…”
Section: Introductionmentioning
confidence: 99%